2022
DOI: 10.1371/journal.pone.0272852
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of copaiba and oregano essential oils on the shelf life of fresh ground beef patties under display: Evaluation of their impact on quality parameters and sensory attributes

Abstract: The preservative effect of the addition of different essential oils (copaiba and oregano) on meat quality parameters and sensorial acceptability was analyzed for fresh ground beef patties over 21 days of display. Five treatments were assessed: control (CON) without antioxidants; addition of the synthetic additive butylated hydroxytoluene (BHT); addition 0.05% of copaiba essential oil (CEO); 0.05% of oregano essential oil (OEO); or blend of 0.025% copaiba and 0.025% oregano essential oils (BEO). The lowest cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…These data agree with previous studies that reported a significant reduction of redness after the incorporation of Moringa seeds on beef burgers and green tea on hamburgers (Al-Juhaimi et al, 2016;Fachinello et al, 2018). Meanwhile, other authors demonstrated a slight reduction of redness after the incorporation of oregano essential oil into beef burgers (Leite et al, 2022), and turmeric powder into chorizo (Hleap-Zapata et al, 2020). The addition of turmeric also increased the yellowness (b*) of the fish patties, and this agreed with the study by Mancini et al (2015), who showed a significantly higher yellowness value in turmeric treated-rabbit burgers.…”
Section: Colour Propertiessupporting
confidence: 92%
“…These data agree with previous studies that reported a significant reduction of redness after the incorporation of Moringa seeds on beef burgers and green tea on hamburgers (Al-Juhaimi et al, 2016;Fachinello et al, 2018). Meanwhile, other authors demonstrated a slight reduction of redness after the incorporation of oregano essential oil into beef burgers (Leite et al, 2022), and turmeric powder into chorizo (Hleap-Zapata et al, 2020). The addition of turmeric also increased the yellowness (b*) of the fish patties, and this agreed with the study by Mancini et al (2015), who showed a significantly higher yellowness value in turmeric treated-rabbit burgers.…”
Section: Colour Propertiessupporting
confidence: 92%
“…The composition of meat can cause rapid LA and PA, leading to a shorter shelf-life and poor quality proteins, resulting in economic losses for the meat industry [ 17 , 37 ]. In industrialized countries, there is a demand for healthier, high-quality proteins with a longer shelf-life [ 21 ].…”
Section: Introductionmentioning
confidence: 99%